Low-density organic silicon-polyurethane encapsulating material as well as preparation method and application thereof
By using low-density organic silicon-polyurethane composite material preparation, the problem of lack of performance of new energy battery irrigation and sealing in existing technologies in existing technologies, insufficient performance in high humidity and heat and impact environment, and achieve higher humidity resistance, bonding, bonding, bonding The strength and flame retardant performance significantly improve the safety performance of the battery module.
Patent Information
- Application Number
- CN202310926159.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
The existing new energy battery potting glue shows low humidity and heat resistance, low bond strength and ineffective barriers to leakage and heat of the battery cell in high humidity and heat, resulting in insufficient safety performance of the battery module.
Using low-density organic silicon-polyurethane composite irrigation materials, the material is used through the appropriate component proportions and foaming agents to prepare an irrigation and seal with a specific closing rate, increase its rebound rate and toughness, enhance impact and impact and impact and impact and impact and impact Hot stability.
It significantly improves the humidity and heat resistance, bonding strength and flame retardant performance of the irrigation and sealing, which can effectively block the leakage and calories of the cells, and significantly improve the safety performance of the battery module.
Smart Images

Figure CN119371624A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a low-density (foam) organic silicon-polyurethane composite potting material and a preparation method and application thereof. The (foam) potting material (which forms a potting glue after curing) is used for the assembly and packaging of new energy battery modules, belonging to the new energy battery packaging technology. Background Art
[0002] With the advent of the electrification era, new energy batteries have become the hottest and most cutting-edge technology field through various packaging (PACK) forms. New energy batteries are widely used in new energy vehicles, energy storage battery packs, fast battery replacement and other industries.
[0003] Major battery cell manufacturers and packaging manufacturers at home and abroad are constantly increasing the energy density of battery packs. Safety issues such as leakage, short circuit, and explosion are increasingly becoming a shackle restricting the development of the new energy industry.
[0004] In the process of new energy battery packaging (packing), many composite functional materials will be used, for example: structural adhesive is used for bonding and fixing of battery cells; thermal conductive adhesive is used to dissipate heat when the battery pack is working, and they play a protective role in the new energy battery pack.
[0005] However, in the new energy industry, whether it is the automotive industry, fast battery replacement, or energy storage industry, battery packs (battery components) are core components. Only by ensuring the safety of battery modules can the safety of life and property of users be guaranteed.
[0006] The durability, permanence, flame retardancy, impact resistance and non-corrosiveness of the potting material are the guarantee of the safety of new energy battery packs.
[0007] At present, in the energy storage, commercial vehicle and application directions of cylindrical batteries, due to the difficulty of production and the cost of potting products, most of the cells do not have potting functional materials. In the application process of battery packs, due to the quality problems of the products themselves and the application environment, some cells are damaged, leaked, short-circuited and caused severe fires, causing huge losses to the personal and property safety of users.
[0008] Currently, the molding (curing) time of silicone potting glue is long and the efficiency is low; the density of silicone potting glue is large and the application cost is high; the bonding effect of silicone potting glue is poor.
[0009] In addition, epoxy resin potting glue is not resistant to temperature differences, has too high hardness, and is weak in withstanding cold and heat shocks.
[0010] CN116003868A discloses a preparation process of power battery thermal insulation cotton with improved rebound rate, comprising the following steps: S1, selecting 45-65 parts by weight of polyurethane, 5-15 parts by weight of tetraethoxysilane, 2-10 parts by weight of foaming agent, 22-29 parts by weight of polyester polyol and 5-8 parts by weight of stabilizer and setting them aside; S2, using tetraethoxysilane as a precursor for gelation, aging, drying and modification to produce silica aerogel and setting them aside; S3, adding polyurethane, foaming agent, polyester polyol and stabilizer into a reactor in sequence and premixing them quickly to produce a premix; S4, applying the premix to both sides of the silica aerogel, and placing the silica aerogel in a molding box for preliminary curing to produce a blank; S5, taking out the blank, hot-pressing and molding the blank, and then trimming it to produce thermal insulation cotton with a specified shape. The foaming agents are sodium bicarbonate, salicylic acid and phthalic acid, and the weight ratio of sodium bicarbonate, salicylic acid and phthalic acid is 10:5:3. The stabilizers are sodium fatty alcohol ether sulfate and polyether modified silicone oil, and the weight ratio of sodium fatty alcohol ether sulfate and polyether modified silicone oil is 2:1. The drying process adopts supercritical drying technology. During supercritical drying, the pre-pressurization range is 7.0-9.0MPa, the supercritical temperature range is 250-275℃, and the supercritical pressure range is 10-12MPa. The thickness of the produced silica aerogel ranges from 2-8mm. However, the thermal insulation cotton of CN116003868A still cannot solve the problems of low bonding strength and inability to fully block the heat generated by leakage and fire of the battery cell, and thus cannot significantly improve the safety performance of the battery module.
[0011] In order to meet the application of polyurethane thermal conductive potting adhesive in the latest automotive battery packs, it is particularly urgent to improve the moisture and heat resistance and impact resistance of polyurethane thermal conductive potting adhesive.
[0012] In addition, for the potting glue used in existing new energy power batteries, when hard foam is used, it can meet the strength requirements, but it has a certain brittleness and poor stability at low temperature (-20°C). When soft foam is used, it can meet the resilience requirements, but the open porosity of the foam is too high (making the water absorption rate too high and the softness too high), the high temperature (70°C) stability is poor, and the supporting force for fixing the battery pack in place is reduced, and the ability to resist impact and vibration will be reduced. Summary of the invention
[0013] In order to solve the technical problems existing in the prior art, the inventor of the present application first provides a fast-curing organic silicon-polyurethane composite potting material and a preparation method thereof, which is used for the assembly and packaging of new energy battery modules. The organic silicon-polyurethane material comprises two components, component A and component B. Components A and B are respectively contained in different sealed containers.
[0014] The silicone-polyurethane of the present invention has the properties of both polyurethane and silicone, and has the properties of being lightweight, waterproof, oxygen-isolating, shock-absorbing, sealing, mildew-proof, insulating, anti-aging, and flame-retardant. It can effectively block the heat generated by leakage and fire of the battery cell and improve the safety performance of the battery module.
[0015] The technical solution of the present invention combines the advantages of silicone materials and polyurethane materials to produce a potting adhesive that has the characteristics of high conductivity, resilience, tear resistance, high temperature resistance, insulation, etc. of silicone; at the same time, it also has the characteristics of light weight, shock resistance, low modulus, anti-vulcanization, and high bonding strength of polyurethane materials.
[0016] The inventors of the present application provide a low-density silicone-polyurethane potting material. The potting glue obtained by foaming and curing the material has a specific closed-cell rate (i.e., a suitable open-cell rate provides a small amount of resilience for the low-density potting glue), thereby meeting the requirements for strength and impact resistance and shock absorption of the potting glue used in the field of new energy vehicle batteries.
[0017] In this application, "optional" means with or without.
[0018] According to a first embodiment of the present invention, a low-density (foam) silicone-polyurethane composite potting material (referred to as a potting composition) (for new energy batteries) is provided, wherein the potting material comprises component A and component B or consists of components A and B:
[0019] Component A includes, by weight:
[0020] Oligophenylene ether diol (PPO) with a number average molecular weight in the range of 800-2500: 30-40 parts; preferably 32-38 parts; 34-36 parts; polytetrahydrofuran ether diol with a number average molecular weight in the range of 800-2200: 10-20 parts; preferably 12-18 parts; preferably 14-16 parts;
[0021] Amino-containing silane coupling agent: 1-4 parts; preferably 1.2-3.8 parts; 1.5-3.5 parts; 1.8-3.2 parts; 2-3 parts;
[0022] Aqueous alcohol amine foaming agent: 6-12 parts; preferably 6.5-11.5 parts; 7-11 parts; 8-10 parts;
[0023] Catalyst: 0.4-2.5 parts; preferably 0.5-2.2 parts; 0.6-2.0 parts; 0.7-1.8 parts; 0.8-1.6 parts; such as 1 or 1.2 parts;
[0024] Halogen-free flame retardant: 8-35 parts; preferably 10-33 parts; 12-30 parts; 15-28 parts; 17-25 parts;
[0025] Foam stabilizer: 1-3 parts; preferably 1.2-2.8 parts; 1.5-2.5 parts; such as 1.8, 2, 2.2 parts;
[0026] Diol chain extender: 0-4 parts; preferably 0.1-3.8 parts, 0.5-3.6 parts; 0.8-3.5 parts; 1-3.2 parts; 1.5-3 parts;
[0027] Antioxidant: 0-2.5 parts; preferably 0.3-2.3 parts; 0.5-2.0 parts; 0.6-1.8 parts; 0.8-1.6 parts;
[0028] Color paste: 0-0.7 parts; preferably 0.1-0.6 parts; 0.15-0.55 parts; 0.2-0.5 parts;
[0029] Component B includes, by weight:
[0030] NCO-terminated polysiloxane-polyurethane prepolymer: 40-50 parts; preferably 42-48 parts; 44-46 parts; such as 45 parts;
[0031] Organic polyisocyanate monomer: 0-7 parts, preferably 1-6 parts; preferably 1.5-5 parts; preferably 2-4.5 parts;
[0032] Viscosity reducer: 8-20 parts; preferably 9-18 parts; 10-17 parts; 11-16 parts; or 12-15 parts.
[0033] When used (for example, in potting applications or in casting applications), component A and component B are mixed, stirred, foamed and potted in a weight ratio of 100:150-70 (i.e., 100:150-100:70), preferably, in a ratio of 100:140-80, 100:130-90, 100:120-100, 100:115-105. That is, components A and B are mixed, stirred, mixed in the above ratio, and the mixture is poured into the battery module to be potted, and it is foamed and potted. After that, the potted battery module is formed.
[0034] The NCO-terminated polysiloxane-polyurethane prepolymer is formed by reacting (in molar excess) an organic polyisocyanate monomer (such as MDI, TDI, HDI and / or IPDI, or trimers thereof, or PMDI) with a polydimethylsiloxane diol (i.e., α,ω-dihydroxy polydimethylsiloxane, or hydroxyl-terminated polydimethylsiloxane). The hydroxyl equivalent weight (HEW) of the polydimethylsiloxane diol is in the range of 400-600 g / mol, preferably 420-580 g / mol, preferably 440-560 g / mol, preferably 450-550 g / mol, preferably 460-540 g / mol, preferably 470-530 g / mol.
[0035] The oligophenylene ether diol (PPO) having a number average molecular weight in the range of 800-2500 (preferably in the range of 900-2200, preferably 950-2000, more preferably 1000-1700) has the following general formula (I) or (II):
[0036]
[0037]
[0038] wherein each R independently represents hydrogen or a C1-C5 alkyl group, and n, X, and Y each represent the number 0 or an integer from 1 to 25, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25; provided that X and Y are not 0 at the same time.
[0039] Preferably, the oligophenylene ether diol (PPO) having a number average molecular weight in the range of 800-2500 (preferably in the range of 900-2200, preferably 950-2000, more preferably 1000-1700) has the following general formula (I) or (II):
[0040]
[0041] The polyphenylene ether (PPO) molecular chain has good heat resistance, weather resistance, and good bonding strength to metal surfaces.
[0042] Polytetramethylene glycol is beneficial to improving the toughness and weather resistance of the potting material. The polytetramethylene glycol with a number average molecular weight of 800-2200 is preferably a polytetramethylene glycol with a number average molecular weight of 1000-2000.
[0043] As the silane coupling agent containing amino group, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792,), and / or 3-aminopropyltriethoxysilane (KH-550) can be used. Silane coupling agent has good bonding strength to metal surface.
[0044] The aqueous alcoholamine blowing agent includes ethanol isopropanolamine, ethanol diisopropanolamine and water, and a portion of the alcoholamine is neutralized by CO2 so that the content of CO2 in the aqueous alcoholamine blowing agent is 1-5.5wt%, preferably 1.2-5.3wt%, 1.5-5.2wt%, preferably 1.8-5.0wt%, preferably 2-4.8wt%, based on the total weight of the aqueous alcoholamine blowing agent. The molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine is (0.2-6):1, preferably (0.25-5.5):1, preferably (0.3-5):1, preferably (0.4-4.5):1, preferably (0.5-4):1, preferably (0.6-3.8):1, preferably (0.7-3.7):1, preferably (0.8-3.6):1, preferably (1.0-3.5):1, preferably (1.1-3.3):1, preferably (1.5-3):1, preferably (1.7-2.8):1, preferably (2.0-2.6):1, preferably (2.2-2.4):1. In the aqueous alcoholamine blowing agent, the water content is 8-29wt%, preferably 16.5-29wt%, preferably 17-28.5wt%, preferably 18-28wt%, preferably 19-27wt%, preferably 20-26wt%, preferably 21-25wt%, based on the total weight of the aqueous alcoholamine blowing agent.
[0045] Preferably, the total content of ethanol isopropanolamine, ethanol diisopropanolamine and water in the aqueous alcohol amine blowing agent is 93-100%, preferably 93.5-100%, preferably 94-100%, preferably 94.5-100%, preferably 95-100%, preferably 95.5-100%, preferably 96-100%, such as 97, 98, 99, 99.5 or 99.8% or 99.9%, based on the total weight of the aqueous alcohol amine blowing agent; preferably, the balance is CO2.
[0046] The catalyst is one or more of N,N-dimethylcyclohexylamine, N,N-dimethylbenzylamine, bis(dimethylaminoethyl)ether and dibutyltin dilaurate.
[0047] The halogen-free flame retardant is one or more of dimethyl methylphosphonate, diethyl ethyl phosphate, triethyl phosphate, isopropylated triphenylphosphonate, triphenyl phosphate, melamine, magnesium hydroxide, ammonium polyphosphate, red phosphorus, expanded graphite, and antimony dioxide. It does not contain halogen and can reduce corrosion to metal parts.
[0048] Preferably, the foam stabilizer is one or more of polymethylsiloxane, amino-modified siloxane, epoxy-modified siloxane, polyether-modified siloxane and sulfur-modified siloxane.
[0049] The diol chain extender is one or more of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, hydroquinone dihydroxyethyl ether and resorcinol dihydroxyethyl ether.
[0050] The antioxidant is one or more of poly(dipropylene glycol) phenyl phosphite, tris(2,4-di-tert-butylphenyl) 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate phosphite, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.
[0051] The color paste is one of oily polyether type black paste, yellow paste, red paste, blue paste, green paste and gray paste.
[0052] The organic polyisocyanate is MDI (diphenylmethane diisocyanate), PMDI (polymethylene polyphenyl polyisocyanate, such as PM200 of Wanhua Chemical), TDI (toluene diisocyanate), HDI (hexamethylene diisocyanate) and / or IPDI (isophorone diisocyanate).
[0053] The viscosity reducer is silicone oil (preferably dimethyl silicone oil), one or more of dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, and tributyl citrate. Silicone oil has the effect of plasticizing and reducing viscosity, and is also beneficial to improving the hydrophobicity of the potting material. Preferably, the viscosity reducer is a combination or mixture of (di)methyl silicone oil and one or more selected from dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, and tributyl citrate.
[0054] According to a second embodiment of the present invention, a method for preparing (or preparing) the above-mentioned low-density (foam) silicone-polyurethane composite potting material (hereinafter referred to as potting composition) is provided, the method comprising:
[0055] Add oligophenylene ether diol (PPO), polytetramethylene ether diol, amino-containing silane coupling agent, halogen-free flame retardant, foam stabilizer, optional chain extender, optional antioxidant, and optional color paste into a reaction kettle, heat the reaction kettle to 105-120° C. (e.g., 110° C.) under stirring to dissolve all the materials in the kettle, evacuate the kettle to negative pressure (e.g., open a vacuum device to evacuate the kettle. Evacuate the kettle to a pressure of, for example, -0.7 MPa to -0.95 MPa, such as -0.8 to -0.9 MPa), and keep the temperature and pressure (i.e., keep the temperature and vacuum degree at 40-200 min, such as 60-150 min, such as 80 min); then, cool to room temperature, release the pressure, add an aqueous alcohol amine foaming agent and a catalyst, and mix again (e.g., 30-180 min, such as 40-150 min, 60-80 min) to obtain component A.
[0056] Add the NCO-terminated polysiloxane diol prepolymer and the viscosity reducer into the reaction kettle, stir, heat the contents in the kettle to 95-105° C. (e.g., 100° C.) and keep the temperature constant for 30-200 min (e.g., 45-150 min, e.g., 60-80 min), evacuate the kettle to negative pressure (e.g., start a vacuum device to evacuate the kettle. Evacuate the kettle to a pressure of, for example, -0.7 MPa to -0.95 MPa, e.g., -0.8 to -0.9 MPa). ), keep the temperature and pressure at the temperature and pressure (i.e., keep the temperature at 95-105°C, such as 100°C and the pressure in the kettle at, for example, -0.7MPa to -0.95MPa, such as -0.8 to -0.9MPa) (for a period of time, for example, 40-180min, such as 50-150min, such as 60-80min), release the pressure, and cool the materials in the kettle (for example, cool the materials in the kettle to 15-40°C, preferably 25-35°C, such as 30°C) to obtain component B.
[0057] The above-mentioned component A and component B are respectively placed in respective containers to obtain a two-component (low-density) organic silicon-polyurethane composite potting material (referred to as potting composition).
[0058] A method for potting a battery module using the above-mentioned low-density (foam) silicone-polyurethane composite potting material (hereinafter referred to as potting composition), the potting method comprising:
[0059] According to the ratio of component A to component B of 100:150-70 (i.e. 100:150-100:70), preferably 100:140-80, 100:130-90, 100:120-100, 100:115-105 (the weighed mass is calculated according to the bulk density of 280), components A and B are mixed and stirred, and the resulting mixture is poured into the battery module to be encapsulated, and it is foamed and encapsulated.
[0060] The present invention also provides a battery module, wherein the above-mentioned encapsulation material is used for encapsulation and molding.
[0061] Advantages of the present invention
[0062] 1. The present invention selects bifunctional polyphenylene ether (dihydroxy PPO) with excellent performance in high temperature resistance, corrosion resistance, weather resistance, acid and alkali resistance, etc. and polytetramethylene ether diol with slightly lower cost and better weather resistance as the main components of component A, with the purpose of providing excellent comprehensive performance for the low-density potting glue after curing when the new energy vehicle battery is running under high humidity and frequent impact conditions, such as high temperature resistance, weather resistance and prevention of corrosion caused by battery leakage liquid.
[0063] 2. When the water content in the aqueous alcohol amine foaming agent is greater than 16.5wt%, preferably greater than 17wt%, more preferably greater than 18wt%, for example, in the range of 16.5-29wt% or in the range of 17-28.5wt% or preferably in the range of 18-28wt%, a portion of the water reacts with the isocyanate group during the foaming process, thereby generating a certain open porosity in the cured potting glue foam, allowing the open porosity to be controlled within the ideal range of 4-10%. Accordingly, the closed porosity of the potting glue foam is controlled within 90-96%, which enables the potting glue foam to have an ideal rebound rate of 6-12%, thereby reducing the brittleness of the foam, increasing toughness or elasticity, having excellent high temperature stability and low temperature stability, and being able to fully resist the effects of impact and vibration. In addition, ethanol diisopropanolamine in the aqueous alcohol amine foaming agent is used as a crosslinking agent to improve the strength of the potting glue. Ethanol isopropanolamine is mainly used to absorb CO2 and is used as a chain extender in the foaming reaction.
[0064] Of course, water content as low as 8 wt% can be used or included in the aqueous alcohol amine blowing agent, for example, its water content is 8-16 wt% or 8-29 wt%, such as 9, 10, 11, 12, 13, 14, 15, 15.5 wt%. However, lower water content is not preferred because the brittleness of the obtained foam will increase and the low temperature stability will deteriorate when the water content is too low. In addition, generally, the water content is not higher than 29 wt%, preferably not higher than 28 wt%.
[0065] In addition, the content of CO2 in the aqueous alcohol amine foaming agent should not be too high, for example, should not be higher than 7wt%, preferably not higher than 6.5wt% or 6wt%. If the content of CO2 is too high, the heat of reaction in the foaming reaction causes a large amount of CO2 to be violently released and expanded, and the opportunity for water to participate in the foaming reaction in the early stage of the foaming reaction will be reduced, thereby affecting the structure of the foam, and further affecting the toughness and strength of the foam.
[0066] 3. The activity of polydimethylsiloxane diol (i.e., α, ω-dihydroxy polydimethylsiloxane) in reacting with isocyanate is slightly low, which affects the curing speed of the potting material. However, if it is made into an NCO-terminated polyurethane prepolymer, the curing rate can be increased. The use of amino-containing silane coupling agents can improve the bonding strength of the potting compound to the metal. The viscosity reducer is mainly dimethyl silicone oil, which is used to reduce the viscosity of component B. The use of these three silicon-containing raw materials is conducive to improving the hydrophobicity of the potting compound.
[0067] 4. The silicone-polyurethane potting material of the present invention has the characteristics of both polyurethane and silicone, and has the characteristics of light weight, waterproof, oxygen isolation, shock absorption, sealing, mildew resistance, insulation, anti-aging, flame retardancy, etc. It can effectively block the heat generated by battery leakage and fire, and greatly improve the safety performance of the battery module. During the driving process of new energy vehicles, the battery module is frequently subjected to impact and vibration, as well as thermal shock in hot weather, battery leakage, etc. Therefore, there are quite high requirements for the bonding strength, heat resistance, impact resistance, thermal insulation, and resilience of the potting glue under harsh conditions. The potting material (potting glue foam) of the present invention has excellent bonding strength for various components in the battery module, and the potting glue foam has sufficient toughness, resilience, flame retardancy, and thermal insulation performance to meet these strict requirements.
[0068] 5. Combine polyurethane and silicone materials to achieve a composite material that has both the lightweight properties of polyurethane and the anti-aging properties of silicone. Although high-performance and high-cost main materials are used, the overall density of the foamed glue is reduced by using polyurethane foaming, thereby greatly reducing production and use costs.
[0069] 6. The potting material has a low thermal conductivity. The potted battery module can block heat conduction during thermal runaway and control heat spread. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 This is a SEM photograph of the potting foam of Example 1.
[0071] Figure 2 This is a SEM photograph of the potting foam of Comparative Example 1.
[0072] Figure 3 The sample of the olamine product of Synthesis Example 4 is 1 H-NMR spectrum. DETAILED DESCRIPTION
[0073] The present invention further describes the technical scheme in detail through the following examples, but the present invention is not limited to these examples.
[0074] Unless otherwise specified, the devices and materials used in the examples are those commonly used in the art and commercially available on the market.
[0075] For oligophenylene ether diols (PPO) with a number average molecular weight in the range of 800-2500, commercially available products can be used, such as the SN-100, SN-115 and SN-125 series of Guangdong Junlong New Material Technology Co., Ltd., and the Mn molecular weight 1500-2000 product series (PPO-150 or 200) of Hebei Jianxin Biotechnology Co., Ltd., and can also be synthesized according to the method described in Example 2 of CN109517164A, Example 6 of EP0215257A1 and Example 1 of US4521584A.
[0076] As the polytetramethylene ether diol, polytetramethylene ether diol having a number average molecular weight of 800-2200, preferably 1000-2000, such as PTMG1000 and PTMG2000 of Jinan Yuyi Chemical Co., Ltd. can be used.
[0077] As polysiloxane diols having a hydroxyl equivalent weight (HEW) between 400 and 600 g / mol (e.g., polydimethylsiloxane diol, α,ω-dihydroxy polydimethylsiloxane, or terminal hydroxyl polydimethylsiloxane), hydroxyl-terminated polysiloxanes MCR-C61 (hydroxyl equivalent HEW = 500 g / mol, functionality 2) and MCR-62 (hydroxyl equivalent 2500 g / mol, functionality 2) from Gelest, USA, and Silmer OH Di-100 (hydroxyl equivalent 3500 g / mol, functionality 2) from Sil TECH can be used. In addition, other polysiloxanes for rigid polyurethane foams can also be used, such as B 8465, B8462, B 8467, B 8461, B 8516, B 8476 produced by Degussa, L-6900, L-6910, L-6915, L-6920, L-6980, L-5440 produced by Crompton, SS8005, SS8002 produced by Saxol, DC5950, DC193, DC1598 produced by Air Products, etc. Products produced by Zhejiang Xin'an Chemical Group Co., Ltd., for example, linear polydimethylsiloxane with terminal hydroxyl groups having a molecular weight of 300 to 500.
[0078] As the foam stabilizer, one or more of polymethylsiloxane, amino-modified siloxane, epoxy-modified siloxane, polyether-modified siloxane, and sulfur-modified siloxane can be used. In addition, the following silicone oil-type foam stabilizers or silane surfactants can also be used: B8525 and B8408 of Evonik Degussa (China) Investment Co., Ltd., AK-158, AK-8805, AK-8812, AK-8809, AK-8818 and AK-8860 of Jiangsu Meside Chemical Co., Ltd., DC8545, DC1990, DC5188, DC6070, DC3042 and DC3201 of Gas and Chemicals, and silicone oil 8841 of Shanghai Maihao Chemical Technology Co., Ltd. Non-silane surfactants: LK-221 and LK-443 of Gas and Chemicals.
[0079] The test methods for various parameters of silicone-polyurethane potting foam are carried out with reference to the following Chinese national standards GB:
[0080]
[0081]
[0082] In the above table, the Z direction represents the vertical direction of the foam sample (i.e., the direction perpendicular to the substrate), and the X direction and the Y direction represent two mutually perpendicular directions on the same horizontal plane of the sample.
[0083] Viscosity refers to the dynamic viscosity "centipoise (cP)" at 25°C.
[0084] The 5% thermal weight loss temperature of the encapsulant was measured using a Mettler differential thermal-thermogravimetric analyzer.
[0085] Synthesis example 1
[0086] Preparation of raw material oligophenylene ether diol (PPO):
[0087] 1) Add 3.0 kg of 2,6-dimethylphenol, 0.5 kg of tetramethylbisphenol A, 9.5 kg of toluene and 0.95 kg of methanol to a reaction kettle with a condensation reflux device, stir until the monomers are completely dissolved, add 0.126 kg of branched polyethyleneimine ligand (Mn = 600 ± 20, Aladdin reagent) and 0.0411 kg of cuprous bromide hydrobromic acid solution (preliminarily prepared with 0.003 kg of cuprous oxide and 0.0381 kg of 48% hydrobromic acid), mix well, introduce oxygen (flow rate of 2000 sccm), and react at 40° C. for 150 minutes;
[0088] 2) adding the polymer solution after the reaction into 0.34 L of 10 wt% sodium nitrilotriacetate solution, reacting at 70° C. for 60 minutes, and then removing the aqueous phase by liquid-liquid centrifugation;
[0089] 3) The oil phase obtained by centrifugation in step 2) was concentrated to 9 L under vacuum, and then precipitated by adding 90 L of methanol, filtered, washed with methanol 3 times, and vacuum dried at 80° C. overnight to obtain a double-terminated hydroxyl polyphenylene ether oligomer (PPO-OH) with a hydroxyl functionality of 1.96 and a number average molecular weight of 1650.
[0090] Synthesis example 2
[0091] 10 kg of hydroxyl-terminated polysiloxane MCR-C61 (hydroxyl equivalent HEW=500 g / mol, functionality 2, Gelest Company, USA) and 2.5 kg of isocyanate MDI (Wanhua Chemical) were mixed at 60° C. under nitrogen atmosphere protection and stirred at a stirring speed of 450 rpm for 0.5 hour, then the temperature was raised to 70° C. to continue the reaction until the NCO content of the reaction product was 3.8%, thereby obtaining an NCO-terminated polysiloxane-polyurethane prepolymer (prepolymer 1).
[0092] Synthesis example 3
[0093] Part I: Preparation of single alcohol amines
[0094] 1) 36.6 kg of ethanolamine (molecular weight 61,600 mol) and 16.7 kg of deionized water were added to an autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C. and the pressure was controlled to be no higher than 0.3 MPa. 34.8 kg of propylene oxide (molecular weight 58,600 mol, the molar ratio of propylene oxide to ethanolamine was 1:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 88 kg of the reaction product (alkanolamine hydrate AA1a) was discharged from the reactor. The product was sampled and the content of ethanol isopropanolamine in the alkanolamine hydrate AA1a was measured by gas chromatography to be 599.7 mol and 0.3 mol of ethanol diisopropanolamine. Its viscosity (30° C.) was 283 centipoise. The water content in the alkanolamine hydrate AA1a was 18.9 wt%. The pH value was 12.43.
[0095] 2) 30.5 kg of ethanolamine (molecular weight 61,500 mol) and 20.58 kg of deionized water were added to the autoclave, stirred and dissolved, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95 ° C, and the pressure was controlled to be no higher than 0.3 MPa. 58 kg of propylene oxide (1000 mol, the molar ratio of propylene oxide to ethanolamine was 2:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40 ° C. Then, 109 kg of the reaction product (alkanolamine hydrate AAxa) was discharged from the reactor, and a sample was taken from the product and the content of ethanol diisopropanolamine in the alkanolamine hydrate AAxa was measured by gas chromatography to be 499.7 mol, and the content of ethanol isopropanolamine was 0.3 mol. Its viscosity (25 ° C) was 390 centipoise. The water content in the alkanolamine hydrate AAxa was 18.8 wt%. pH value = 11.72.
[0096] Part 2: Compounding
[0097] Four batches of 20 kg were taken from 88 kg of the reaction product (alcoholamine hydrate AA1a). For each batch, 20 kg of the reaction product (alcoholamine hydrate AA1a, 136.3 mol of ethanol isopropanolamine) was added to a high-pressure reactor, and then alkanolamine hydrate AAxa (water content of 18.8 wt%) and water were added, and the mixture was mixed according to the molar ratio and water content in Table 1 below to obtain four batches of alkanolamine compositions AC (AA1b-AA1e).
[0098] Table 1: Molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine
[0099]
[0100] Part 3: CO2 Neutralization and Salt Formation
[0101] The four batches of alcohol amine hydrates AA1b-AA1e obtained by the above compounding were added to the autoclave respectively, and carbon dioxide gas was introduced into the alcohol amine hydrates AA1b-AA1e respectively under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder was controlled to be not higher than 0.3MPa, and the temperature was controlled between 40-50°C, and the temperature was controlled to react for 3 hours, and the pressure was released after the temperature was lowered to below 40°C, and then a small amount of water was added to make the water content in the carbonate alcohol amine salt composition reach 21wt%, and the mixture was slowly stirred for 30 minutes, and the product was discharged, thereby obtaining carbonate alcohol amine salt compositions AA2b-AA2e (or carbonate alcohol amine salt compositions 1-4). The CO2 content is shown in Table 2.
[0102] Table 2: CO2 content in carbonate amine salt compositions
[0103]
[0104] Synthesis example 4
[0105] 24.64 kg of ethanolamine (molecular weight 61, 404 mol) and 12.24 kg of deionized water were added to a high-pressure reactor, stirred to dissolve, and the reactor was sealed. Then, under continuous stirring, the temperature was controlled between 60-95° C., and the pressure in the reactor was controlled not to be higher than 0.3 MPa. 41.8 kg of propylene oxide (molecular weight 58, 720 mol, the molar ratio of propylene oxide to ethanolamine was 1.8:1) was added to the reactor in batches. After the addition of the materials, the temperature was controlled to react for 3 hours, and then the temperature was lowered to 40° C. Then, 78.64 kg of the reaction product (alcoholamine hydrate AA3a, or alcoholamine composition AA3a) was discharged from the reactor, and the viscosity (25° C.) was 288 centipoise. The product was sampled and the content of ethanol isopropanolamine in the amine hydrate AA3a was measured by gas chromatography. The content of ethanol diisopropanolamine was 80.9 mol, the content of ethanol diisopropanolamine was 323.1 mol, and the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine was 4:1. 1 H-NMR spectrum is shown in Figure 3 The water content of the alcoholamine hydrate AA3a was determined by Karl Fischer method to be 15.6 wt %.
[0106] Then, 40 kg of the above obtained alcohol amine hydrate AA3a is added to the autoclave, and carbon dioxide gas is introduced into the alcohol amine hydrate AA3a under the condition that the pressure of the CO2 gas output from the CO2 storage cylinder is not higher than 0.3 MPa, and the temperature is controlled between 40-50°C, and the temperature is controlled to react for 3 hours. After the temperature is lowered to below 40°C, the pressure is released and the product is discharged to obtain a carbonate alcohol amine salt composition AA3b (or alcohol amine composition AA3b), wherein the CO2 absorption is 1.76 kg (about 40 mol; CO2 content is 4.2 wt%). The dynamic viscosity (25°C) of the product AA3b is 792 centipoise. The pH of the product AA3b measured by a pH meter (Ray Magnetic PHS-3C type, Shanghai Yidian Science Instrument Co., Ltd.) is 10.6. Its decomposition temperature is between 45°C and 60°C.
[0107] Example 1
[0108] 3.5 kg of double-terminated hydroxyl polyphenylene ether oligomer (PPO-OH), 1.5 kg of polytetramethylene ether glycol (PTMG1000 from Jinan Yuyi Chemical Co., Ltd.), 0.25 kg of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (YJ-602, Shandong Yuanjin New Materials Co., Ltd.), 1 kg of dimethyl methylphosphonate and 1 kg of melamine (halogen-free flame retardant), 0.15 kg of foam stabilizer DC3201 (Gas and Chemicals Company), 0.01 kg of 1,4-butanediol as a chain extender, 0.1 kg of antioxidant poly(dipropylene glycol) )phenyl phosphite is added into the reaction kettle, stirring is started, the speed is set to 100 rpm, the heating device is turned on to heat the material in the kettle to 110°C, and then the constant temperature is maintained for 60 minutes, the vacuum device is turned on to the pressure in the kettle to -0.9MPa, and the temperature and pressure are maintained for 80 minutes, the pressure is released (the vacuum is released), the material in the kettle is cooled to 30-35°C, 0.1kg of catalyst N,N-dimethylcyclohexylamine and 0.9kg of carbonate amine salt composition 1 (AA2b) as an aqueous alcoholamine foaming agent are added, and mixed for another 60 minutes to obtain component A with a viscosity (25°C) of 1490mPa.s.
[0109] 4.5 kg of NCO-terminated polysiloxane-polyurethane prepolymer (prepolymer 1), 0.4 kg of HDI trimer HT-100 (Wanhua Chemical, functionality 3), 1.3 kg of dimethyl silicone oil (GB201-350, Jinan Silicon Port Chemical Co., Ltd.) and 0.2 kg of dimethyl phthalate were added to the reactor, stirring was started, the speed was set to 100 rpm, the heating device was turned on, the temperature of the material in the reactor was raised to 100°C, the constant temperature was maintained for 60 minutes, the vacuum device was turned on until the pressure in the reactor was -0.9 MPa, and after keeping the temperature and pressure for 60 minutes, the pressure was released and the temperature of the material in the reactor was lowered to 30°C to obtain component B.
[0110] The component A and component B prepared by the above method are mixed in a weight ratio of 100:110, wherein the weight is calculated according to the bulk density of 280; the stirrer is turned on and the stirrer speed is set at 2800 rpm, mixed for 20 seconds, and the mixture is poured into the lithium-ion battery module to be potted, foamed, and potted. The potted battery module is thus formed.
[0111] At the same time, in order to test the performance of the potting compound, the mixture was poured into a plastic box and allowed to foam and solidify. Then the performance of the potting compound was analyzed by sampling, and the measured properties are listed in Table 3. The thermal conductivity (w / m·k, 22.5°C) is 0.02218. The flame retardancy meets the UL94-V0 standard. The temperature of 5% thermal weight loss is 268°C. The SEM photo of the foam sample is shown in Figure 1 In the experiment, the size of the pores is uniform, the outline of the pores is clear, and the integrity is good.
[0112] Example 2
[0113] Example 1 was repeated except that the same amount of carbonate alcohol amine salt composition 2 (AA2c) was used instead of carbonate alcohol amine salt composition 1 (AA2b).
[0114] Example 3
[0115] Example 1 was repeated except that the same amount of carbonate alcohol amine salt composition 3 (AA2d) was used instead of carbonate alcohol amine salt composition 1 (AA2b).
[0116] Comparative Example 1 (Com.Ex 1)
[0117] Example 1 was repeated except that the same amount of carbonate alcohol amine salt composition 4 (AA2e) (water content 32 wt%) was used instead of carbonate alcohol amine salt composition 1 (AA2b). The SEM photograph of the foam sample is shown in Figure 2 In the embodiment, the size of the pores is uneven, and the number of through pores is large (higher open porosity).
[0118] Comparative Example 2 (Com.Ex.2)
[0119] Example 1 was repeated except that the same amount of carbonate amine salt composition AA3b (water content about 15 wt%) was used instead of carbonate amine salt composition 1 (AA2b).
[0120] Table 3-Performance parameters of potting foam
[0121]
[0122] Note: The compressive strength is measured on the foam specimen in the Z direction (perpendicular to the substrate).
[0123] From the data in Table 3 above, it can be seen that the closed-cell rate of the potting glue of Comparative Example 1 is too low, the water absorption rate is too high, and the rebound rate is especially too high. The high-temperature stability (dimensional stability%, 70°C) deteriorates (up to 1.32), and the impact and vibration on the battery pack cannot be effectively reduced during the operation of the new energy vehicle, resulting in the battery cell being unable to be fixed in place. In other words, conventional semi-rigid or semi-soft polyurethane foams cannot be used for the potting of new energy battery modules. The closed-cell rate of the potting glue of Comparative Example 2 is too high, the hardness is high, the brittleness is slightly large, the rebound rate is low, and the low-temperature stability (dimensional stability%, -20°C) deteriorates (up to 0.50), so it cannot play a protective role for the battery.
[0124] The potting glue of Examples 1-3 of the present invention has a suitable closed-cell rate and rebound rate (6-9%), takes into account both strength and toughness, has good stability at high and low temperatures, and fully exerts its protective effect on the battery. In addition, the potting glue of Examples 1-3 has an extremely low water absorption rate, that is, it has a high hydrophobicity, and can fully prevent the penetration and diffusion of leakage liquid (such as battery cell leakage) of the battery module.
[0125] The potting glue of Examples 1-3 of the present invention can effectively strengthen the integrity of the battery module, has good ability to resist impact and vibration, and improves the insulation performance between electronic components and circuits.
Claims
1. A low-density silicone-polyurethane potting material, the potting material comprising two components, component A and component B, wherein component A comprises, by weight: Oligophenylene ether diol with a number average molecular weight in the range of 800-2500: 30-40 parts; Polytetramethylene glycol with a number average molecular weight of 800-2200: 10-20 parts; Amino-containing silane coupling agent: 1-4 parts; Aqueous alcohol amine foaming agent: 6-12 parts; Catalyst: 0.4-2.5 parts; Halogen-free flame retardant: 8-35 parts; Foam stabilizer: 1-3 parts; Diol chain extender: 0-4 parts; Antioxidant: 0-2.5 parts; Color paste: 0-0.7 parts; Component B includes, by weight: NCO-terminated polysiloxane-polyurethane prepolymer: 40-50 parts; Organic polyisocyanate monomer: 0-7 parts, Viscosity reducer: 8-20 parts; in, The aqueous alcohol amine foaming agent comprises ethanol isopropanolamine, ethanol diisopropanolamine and water, wherein the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine is (0.2-6):1, and wherein a portion of the alcohol amine is neutralized by CO2, so that the content of CO2 in the aqueous alcohol amine foaming agent is 1-5.5wt%, based on the total weight of the aqueous alcohol amine foaming agent; in the aqueous alcohol amine foaming agent, the content of water is 8-29wt%, based on the total weight of the aqueous alcohol amine foaming agent; When used for potting, component A and component B are mixed in a weight ratio of 100:150-70, stirred, foamed and potted.
2. The low-density silicone-polyurethane composite potting material according to claim 1, wherein Component A includes, by weight: Oligophenylene ether diol with a number average molecular weight in the range of 800-2500: 32-38 parts; Polytetramethylene glycol with a number average molecular weight of 800-2200: 12-18 parts; Amino-containing silane coupling agent: 1.2-3.8 parts; Aqueous alcohol amine foaming agent: 6.5-11.5 parts; Catalyst: 0.6-2.0 parts; Halogen-free flame retardant: 10-33 parts; Foam stabilizer: 1.2-2.8 parts; Diol chain extender: 0-3.8 parts; Antioxidant: 0.3-2.3 parts; Color paste: 0-0.6 parts; Component B includes, by weight: NCO-terminated polysiloxane-polyurethane prepolymer: 42-48 parts; Organic polyisocyanate monomer: 1-6 parts, Viscosity reducer: 9-18 parts; in, The aqueous alcoholamine foaming agent comprises ethanol isopropanolamine, ethanol diisopropanolamine and water, wherein the molar ratio of ethanol diisopropanolamine to ethanol isopropanolamine is (0.25-5.5):1, and wherein a portion of the alcoholamine is neutralized by CO2 so that the content of CO2 in the aqueous alcoholamine foaming agent is 1.5-5.2wt%, based on the total weight of the aqueous alcoholamine foaming agent; in the aqueous alcoholamine foaming agent, the content of water is 9-28wt%, based on the total weight of the aqueous alcoholamine foaming agent.
3. The low-density silicone-polyurethane composite potting material according to claim 1 or 2, wherein Component A includes, by weight: Oligophenylene ether diol with a number average molecular weight in the range of 800-2500: 34-36 parts; Polytetramethylene glycol with a number average molecular weight of 800-2200: 14-16 parts; Amino-containing silane coupling agent: 1.5-3.5 parts; Aqueous alcohol amine foaming agent: 7-11 parts; Catalyst: 0.7-1.8 parts; Halogen-free flame retardant: 12-30 parts; Foam stabilizer: 1.5-2.5 parts; Diol chain extender: 0.5-3.5 parts; Antioxidant: 0.5-2.0 parts; Color paste: 0-0.6 parts; Component B includes, by weight: NCO-terminated polysiloxane-polyurethane prepolymer: 44-46 parts; Organic polyisocyanate monomer: 1-5 parts, Viscosity reducer: 10-17 parts.
4. The low-density silicone-polyurethane composite potting material according to any one of claims 1 to 3, wherein When used for potting, component A and component B are mixed in a weight ratio of 100:140-80; and / or The amino-containing silane coupling agent is N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (KH-792,), and / or 3-aminopropyltriethoxysilane (KH-550); and / or The viscosity reducing agent is one or more of silicone oil, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, and tributyl citrate; and / or The NCO-terminated polysiloxane-polyurethane prepolymer is formed by reacting an organic polyisocyanate monomer with polydimethylsiloxane diol, wherein the hydroxyl equivalent weight (HEW) of the polydimethylsiloxane diol is in the range of 400-600 g / mol.
5. The low-density silicone-polyurethane composite potting material according to any one of claims 1 to 4, wherein When used for potting, component A and component B are mixed in a weight ratio of 100:130-90; and / or The viscosity reducing agent is dimethyl silicone oil; and / or The NCO-terminated polysiloxane-polyurethane prepolymer is formed by reacting an organic polyisocyanate monomer with polydimethylsiloxane diol, wherein the hydroxyl equivalent weight (HEW) of the polydimethylsiloxane diol is in the range of 420-580 g / mol; and / or The organic polyisocyanate monomer is diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, toluene diisocyanate, hexamethylene diisocyanate and / or isophorone diisocyanate; and / or In the aqueous alcoholamine blowing agent, the water content is 20-26 wt %, based on the total weight of the aqueous alcoholamine blowing agent; and / or The halogen-free flame retardant is one or more of dimethyl methylphosphonate, diethyl ethyl phosphate, triethyl phosphate, isopropylated triphenylphosphonate, triphenyl phosphate, melamine, magnesium hydroxide, ammonium polyphosphate, red phosphorus, expanded graphite, and antimony dioxide.
6. The low-density silicone-polyurethane composite potting material according to any one of claims 1 to 5, wherein When used for potting, component A and component B are mixed in a weight ratio of 100:120-100; and / or The foam stabilizer is one or more of polymethylsiloxane, amino-modified siloxane, epoxy-modified siloxane, polyether-modified siloxane or sulfur-modified siloxane; and / or In the aqueous alcoholamine blowing agent, the content of water is 10-27 wt % based on the total weight of the aqueous alcoholamine blowing agent.
7. The low-density silicone-polyurethane composite potting material according to any one of claims 1 to 6, wherein The number average molecular weight of the oligophenylene ether diol is in the range of 900-2200; and / or The number average molecular weight of polytetramethylene glycol is in the range of 1000-2000; and / or In the aqueous alcoholamine blowing agent, the content of water is 11-26 wt % based on the total weight of the aqueous alcoholamine blowing agent.
8. The low-density silicone-polyurethane composite potting material according to any one of claims 1 to 7, wherein The oligophenylene ether diol (PPO) with a number average molecular weight in the range of 800-2500 has the following general formula (I) or (II): wherein each R independently represents hydrogen or a C1-C5 alkyl group, and n, X, and Y independently represent the number 0 or an integer from 1 to 25, provided that X and Y are not 0 at the same time; and / or In the aqueous alcoholamine blowing agent, the content of water is 12-25 wt %, preferably 18-24, based on the total weight of the aqueous alcoholamine blowing agent.
9. A method for preparing the low-density silicone-polyurethane composite potting material according to any one of claims 1 to 8, the method comprising: Add oligophenylene ether diol, polytetramethylene ether diol, amino-containing silane coupling agent, halogen-free flame retardant, foam stabilizer, optional chain extender, optional antioxidant, and optional color paste into a reaction kettle, heat to 105-120° C. under stirring to dissolve all the materials in the kettle, evacuate the kettle to negative pressure, keep the temperature and pressure, then cool to room temperature, release the pressure, add aqueous alcohol amine foaming agent and catalyst, and mix to obtain component A; Add the NCO-terminated polysiloxane diol prepolymer and the viscosity reducer into a reaction kettle, stir, heat the contents in the kettle to 95-105° C. and keep the temperature constant for 30-200 min, evacuate the kettle to negative pressure, keep the temperature and pressure at the temperature and pressure, release the pressure, and cool the contents in the kettle to obtain component B; The above-mentioned component A and component B are respectively placed in respective containers to obtain a two-component silicone-polyurethane composite potting material.
10. A battery module, wherein the battery module is potted and molded using the potting material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Synthesis method of double-end hydroxy polyphenylene ether oligomer
CN109517164A
Preparation process of power battery heat insulation cotton capable of improving rebound rate
CN116003868A
Process for the preparation of mono- and bifunctional oligo(phenylene oxides)
EP0215257A1
Process for the production of bifunctional polyphenylene ethers
US4521584A